Green innovation and firm value: The mediating role of financial performance in Indonesian Non-Financial Firms - Inez Rieke Dewanti; Rr. Sri Saraswati (AFRE (Accounting and Financial Review), 2026)
This study examined the effects of green process and green product innovation on firm value, with financial performance serving as a potential mediating mechanism. Financial performance was measured using Return on Assets (ROA) and Return on Equity (ROE), while firm value is assessed using Tobin’s Q. Following financial-data revalidation and outlier treatment, the study utilized a balanced panel dataset of 273 non-financial companies listed on the Indonesia Stock Exchange during 2021–2024, comprising 1,092 firm-year observations. Panel-data regression and Sobel mediation tests are applied to evaluate the proposed relationships. The results indicated that neither green process nor green product significantly affects ROA. Green process showed a marginally significant negative effect on ROE at the 10 percent level, whereas green product has no significant effect on ROE. In terms of firm value, green process showed a significant negative effect, while green product showed a marginally significant negative effect. Furthermore, neither ROA nor ROE significantly influences firm value, and neither variable mediates the relationship between green innovation and firm value. The study integrated Signaling Theory, the Resource-Based View, and Legitimacy Theory to explain how green innovation may function as a non-financial signal, strategic capability, or legitimacy-related activity. The findings implied that environmental initiatives and disclosures are more likely to be valued by investors when they are accompanied by measurable economic outcomes.